1987
DOI: 10.1002/ana.410210413
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human immunodeficiency virus in cerebrospinal fluid of children with progressive encephalopathy

Abstract: The retrovirus that causes acquired immune deficiency syndrome (AIDS) is now designated the human immunodeficiency virus (HIV). The cerebrospinal fluid (CSF) of 27 children with HIV infection was assayed for intra-blood-brain barrier (IBBB) synthesis of HIV-specific antibodies and for the presence of HIV antigen. In this cohort, 11 children had a progressive encephalopathy (PE), 9 had a static encephalopathy (SE), and 7 had normal neurological findings (N). IBBB synthesis of HIV-specific antibodies was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1987
1987
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…In cerebrospinal fluid (CSF), lIIV-Ag appears to be associated with progressive encephalopathy in children (12). In the present study, we report the correlation between HIV-Ag expression in CSF of humans and experimentally infected chimpanzees, intra-blood-brain barrier production of HIVAb, and clinical disease.…”
mentioning
confidence: 66%
“…In cerebrospinal fluid (CSF), lIIV-Ag appears to be associated with progressive encephalopathy in children (12). In the present study, we report the correlation between HIV-Ag expression in CSF of humans and experimentally infected chimpanzees, intra-blood-brain barrier production of HIVAb, and clinical disease.…”
mentioning
confidence: 66%
“…Although some studies have indicated that the presence of CSF HIV-1 p24 antigen is associated with a progressive encephalopathy in children (101,143) and in some adults (142), subsequent studies have failed to confirm that the detection of CSF HIV-1 antigen predicts subsequent neurological deterioration (38,296). Similarly, the isolation of HIV-1 from CSF is not a useful marker for HIV-1 encephalopathy (38).…”
Section: Neuropsychological Testsmentioning
confidence: 99%
“…12 These abnormalities as well as the production within the blood-brain barrier of antibodies recognizing HIV-1 have been identified in both symptomatic and asymptomatic HIV-1 infected children. 16 Children with progressive encephalopathy will, in addition, show the presence of HIV-1 p24 antigen in the CSF.I6 This, unfortunately, occurs too late in the course of disease to be of value progno~tically.~~'~…”
Section: Progressive Encephalopathymentioning
confidence: 99%